2009
DOI: 10.1371/journal.pone.0006482
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Performance of Information Theory-Based Methods and Cross-Correlation to Estimate the Functional Connectivity in Cortical Networks

Abstract: Functional connectivity of in vitro neuronal networks was estimated by applying different statistical algorithms on data collected by Micro-Electrode Arrays (MEAs). First we tested these “connectivity methods” on neuronal network models at an increasing level of complexity and evaluated the performance in terms of ROC (Receiver Operating Characteristic) and PPC (Positive Precision Curve), a new defined complementary method specifically developed for functional links identification. Then, the algorithms better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
206
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(210 citation statements)
references
References 43 publications
(63 reference statements)
3
206
0
1
Order By: Relevance
“…Although fast-scale and electrical connections between individual neurons have been identified by methods such as mutual information, transfer entropy, directed transfer functions, Granger causality, or betweensample analysis of connectivity (BSAC) (27,(38)(39)(40)(41), these methods are not suitable here due to nonstationary gene expression and the slow-scale nature of VIP and GABA feedback to the core oscillator, resulting in the damping of high-frequency signals (16,41,42). High-frequency GABA signals affect the firing of SCN neurons and have been mapped previously (27); however, fast scale GABA is not thought to affect the core oscillator (16).…”
Section: Resultsmentioning
confidence: 99%
“…Although fast-scale and electrical connections between individual neurons have been identified by methods such as mutual information, transfer entropy, directed transfer functions, Granger causality, or betweensample analysis of connectivity (BSAC) (27,(38)(39)(40)(41), these methods are not suitable here due to nonstationary gene expression and the slow-scale nature of VIP and GABA feedback to the core oscillator, resulting in the damping of high-frequency signals (16,41,42). High-frequency GABA signals affect the firing of SCN neurons and have been mapped previously (27); however, fast scale GABA is not thought to affect the core oscillator (16).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a convergence criterion was applied and the final maximum likelihood estimate was obtained by repeating Step 1 and Step 2 until convergence of the fluctuations. In the previous methods [1][2][3], the connection strength is found only between two neurons; in contrast, the proposed method deals with overall relations. In addition the repetitive procedure involving Step 1 and Step 2 is similar to the EM algorithm [7].…”
Section: Fitting To the Izhikevich Modelmentioning
confidence: 95%
“…Estimating connectivity of a network has been an active research area [13,11]. Analyzing cortical neural networks has been one of the prominent examples of this task [10].…”
Section: Connectivity Estimationmentioning
confidence: 99%
“…Okatan et al defined a likelihood function for connectivity and proposed a method of inference [24]. Garofalo et al compared various methods of connectivity estimation and reported that transfer entropy and joint entropy give the best results [11].…”
Section: Connectivity Estimationmentioning
confidence: 99%
See 1 more Smart Citation